2011
DOI: 10.1088/1749-4699/4/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Finding regions of interest on toroidal meshes

Abstract: Fusion promises to provide clean and safe energy, and a considerable amount of research effort is underway to turn this aspiration into reality. This work focuses on a building block for analyzing data produced from the simulation of microturbulence in magnetic confinement fusion devices: the task of efficiently extracting regions of interest. Like many other simulations where a large amount of data are produced, the careful study of "interesting" parts of the data is critical to gain understanding. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is possible to represent the binary image differently to achieve better performance for the connected component labeling step [22]. The key idea is to make the representation of the foreground pixels more compact.…”
Section: Feature Detection On Mesh Datamentioning
confidence: 99%
“…It is possible to represent the binary image differently to achieve better performance for the connected component labeling step [22]. The key idea is to make the representation of the foreground pixels more compact.…”
Section: Feature Detection On Mesh Datamentioning
confidence: 99%
“…In this context, a researcher might be interested in finding ignition kernels, or regions of extinction. On the other hand, when studying the stability of magnetic confinement for fusion, a researcher might be interested in regions with high electric potential because of their association with zonal flows, critical to the stability of the magnetic confinement-as shown in Figure 4a [42].…”
Section: Segmenting Query Resultsmentioning
confidence: 99%
“…By varying the first step, this procedure could be applying to different applications. Earlier, this approach was applied to data from regular meshes [2], [10]. In this work, we will demonstrated that it can also be effectively applied to irregular mesh data.…”
Section: Introductionmentioning
confidence: 90%
“…However, due to noise and lack of a ground truth image, this approach can be sensitive to the setting of parameters, and it is hard to use generic method for all images. In addition, the output from visualization is not convenient to feed into other analysis [2]. The regions of interest computed from this work can be more conveniently fed into other analyses.…”
Section: Blob Detection In Fusion Plasmamentioning
confidence: 99%
See 1 more Smart Citation